Phytomicrobiome engineering for crop growth and resilience - Ahmad Azmi, Nur Sabrina (Humana Press, Springer Nature, 2025)
Phytomicrobiome engineering is a novel method that has the potential to revolutionize crop development and increase agricultural system resilience. This technique creates a comprehensive framework for modifying the phytomicrobiome to optimize plant performance, nutrient utilization, and stress response by leveraging the complicated connections between plants and their associated microbiota. This protocol provides a comprehensive guide for researchers and practitioners seeking to unlock the full potential of plant–microbe interactions for sustainable and resilient crop production by incorporating cutting-edge techniques such as host-mediated microbiome engineering and selective passaging for disease suppression.